2018
DOI: 10.3390/fishes3040047
|View full text |Cite
|
Sign up to set email alerts
|

Potential Human Health Applications from Marine Biomedical Research with Elasmobranch Fishes

Abstract: Members of the subclass of fishes collectively known as elasmobranchs (Class Chondrichthyes, Subclass Elasmobranchii) include sharks, skates, rays, guitarfish, and sawfish. Having diverged from the main line of vertebrate evolution some 400 million years ago, these fishes have continued to be successful in our ever-changing oceans. Much of their success must be attributed to their uncanny ability to remain healthy. Based on decades of basic research, some of their secrets may be very close to benefitting man. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…To date, most studies focused on freshwater species, and little attention was paid to the marine ones. More generally, in the marine environment, while a handful of drugs have been developed from marine invertebrates, marine vertebrates remain largely underutilized as a potential source for new therapeutic agents (Luer and Walsh, 2018). Fishes discarded from fisheries could be a relevant, easily-fond, and low-cost source for the isolation of new biologically active compounds (Hellio et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…To date, most studies focused on freshwater species, and little attention was paid to the marine ones. More generally, in the marine environment, while a handful of drugs have been developed from marine invertebrates, marine vertebrates remain largely underutilized as a potential source for new therapeutic agents (Luer and Walsh, 2018). Fishes discarded from fisheries could be a relevant, easily-fond, and low-cost source for the isolation of new biologically active compounds (Hellio et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Externally, male sharks have paired prolongations of the pelvic fins called claspers (or myxopterygium) used as intromittent organs for internal fertilization [ 13 , 34 , 35 , 36 , 37 ] ( Figure 6 ). Claspers are located at the inner margin of the pelvic fins, forming a tube-like structure with a ventral groove known as hypopyle.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their position as one of the oldest groups of vertebrates [ 30 ], Chondrichthyes have been previously used as animal models for physiological and morphological studies [ 31 , 32 , 33 , 34 ]. Moreover, certain aspects of their reproductive morphology, such as the form and function of their intromittent organs [ 35 , 36 , 37 , 38 ] or gonads [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], have received attention from researchers and are well studied.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have revealed that glycosaminoglycans from sharks have anti‐inflammatory and wound healing properties (Krichen et al 2018; Luer and Walsh 2018) and that their high content of omega‐3 polyunsaturated fatty acids may contribute to muscle regenerative processes (Davidson and Cliff 2002). The current understanding of the physiological role of omega‐3 polyunsaturated fatty acids includes activation of muscle stem cells as well as muscle growth and hypertrophy (Tachtsis et al 2018).…”
Section: Discussionmentioning
confidence: 99%